From Confrontation To Peace (Indonesia-Malaysia relations 1963-1966) - Andre Bagus Irshanto (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2019)
Indonesia and Malaysia are two neighboring countries which experienced ups and downs which initially experienced good relations especially when Malaysia gained independence from the United Kingdom on 31 August 1957 welcomed by Indonesia On 17 April 1959, Indonesia and Malaysia signed a friendship agreement. Relations between the two countries began to be disrupted, especially when differences in political ideology were lived. Relations were increasingly tense especially when Tunku Abdul Rahman tried to form a Malaysian federation consisting of Malaya, Singapore and Sarawak, which was declared on September 16, 1963. Since then the confrontation that began marked by the withdrawal of the Malaysian ambassador on January 30, 1963, and in the development of subsequently in the form of a ceasefire which began on 11 February 1963 and on 3 May 1964 President Sukarno announced the order